2018
DOI: 10.1038/s41467-018-04434-y
|View full text |Cite
|
Sign up to set email alerts
|

X-ray structure of a carpet-like antimicrobial defensin–phospholipid membrane disruption complex

Abstract: Defensins are cationic antimicrobial peptides expressed throughout the plant and animal kingdoms as a first line of defense against pathogens. Membrane targeting and disruption is a crucial function of many defensins, however the precise mechanism remains unclear. Certain plant defensins form dimers that specifically bind the membrane phospholipids phosphatidic acid (PA) and phosphatidylinositol 4,5-bisphosphate, thereby triggering the assembly of defensin–lipid oligomers that permeabilize cell membranes. To u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 49 publications
3
48
0
Order By: Relevance
“…Different authors have suggested several mechanisms for permeabilization of membranes [9,30]. In recent years some of the oligomeric structures of plant AMPs bound to their membrane target have been reported and their structures were deposited in the Protein Data Bank [20,[31][32][33]. We found that most of the peptides in our dataset were predicted to have at least one amyloidogenic region which strengthens our belief that these regions could help the AMPs to form oligomers.…”
Section: Oligomerization Of Ampssupporting
confidence: 84%
“…Different authors have suggested several mechanisms for permeabilization of membranes [9,30]. In recent years some of the oligomeric structures of plant AMPs bound to their membrane target have been reported and their structures were deposited in the Protein Data Bank [20,[31][32][33]. We found that most of the peptides in our dataset were predicted to have at least one amyloidogenic region which strengthens our belief that these regions could help the AMPs to form oligomers.…”
Section: Oligomerization Of Ampssupporting
confidence: 84%
“…Much research has focused on nano- and/or molecular-scale including models including the barrel-stave pore model, toroidal pore model, carpet model, and others by use of transmission electron microscopy, atomic force microscopy, and X-ray scattering. More recent work has highlighted the dynamic nature of some these states, possibly allowing for reversibility as seen in the FRAP data herein 5 , 7 , 53 55 . Other investigations into the mode of action of AMPs and their mimetics have also visualized dramatic, micrometer-scale membrane changes by electron microscopy and confocal microscopy 25 , 56 58 .…”
Section: Discussionmentioning
confidence: 97%
“…In fact, most AMPs display high affinity for microbial membranes resulting from their overall amphipathic nature. Thus, it is not surprising that peptides from other structural classes such as defensins or cyclotides also exhibit potent membranolytic effects [55,56]. Nevertheless, it is becoming more apparent that membraneactive AMPs often act on specific targets rather than via unspecific pore formation.…”
Section: Insert Tablementioning
confidence: 99%